Television’s Ecological Imprint. Serial Narratives and Environmental Awareness - Bernardelli, Andrea; Pescatore, Guglielmo; Sonego, Allegra (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
How do television narratives shape environmental awareness in the Anthropocene? This volume delves into the evolving relationship between serial storytelling and ecological discourse, exploring how contemporary television integrates sustainability, climate change, and environmental crises into its narrative structures. From dystopian science fiction to contemporary dramas, television has become a key medium for reflecting and influencing public perceptions of ecological challenges. While serialized storytelling offers an extended framework for addressing environmental issues, it also presents inherent contradictions. The need to maintain audience engagement often leads to the personalization of systemic ecological crises, shifting the focus from collective action to individual struggles. Yet, these narratives—whether through immersive world-building, speculative fiction, or plot-driven dramas—contribute to shaping a deeper cultural consciousness around sustainability and environmental responsibility. This collection highlights television’s dual role in reflecting and shaping the ecological crisis by weaving together perspectives from ecocriticism, media, and narrative studies. Whether subtly integrated into complex storytelling or placed at the forefront of compelling narratives, environmental themes in serial television offer a vital space for engagement, debate, and reflection on the future of our planet.